The Effects of Aging Time on the Eating Quality of Biceps Femoris Steaks - Mason J. Prester; Lauren M. Frink; Stephanie L. Witberler; Jerrad F. Legako; Dale R. Woerner; Rhonda K. Miller; Chris R. Kerth; Mahesh N. Nair; Jessica M. Lancaster; Travis G. O'Quinn (Kansas Agricultural Experiment Station Research Reports, 2025)
Objective: This study evaluated the sensory, instrumental color, and tenderness characteristics of biceps femoris steaks aged from 14 to 70 days. Study Description: Beef sirloin top butt sub-primal cuts (n = 80) were collected from a commercial processing facility and aged at 35.6°F and 39.2°F throughout the duration of their aging periods. After aging, the biceps femoris and gluteus medius muscles were separated, and 1-in thick steaks were fabricated, packaged, frozen at -4°F, and stored for subsequent analysis. The steaks underwent instrumental evaluations for raw and cooked color traits, tenderness, and consumer sensory preferences. Results: There were no differences (P > 0.05) in the percentage of samples rated acceptable for flavor, juiciness, tenderness, or overall. Moreover, there were no differences (P > 0.05) in flavor, juiciness, tenderness, or overall liking among the different aging periods. Furthermore, no differences (P > 0.05) were observed in the percentage of cook loss, Warner Bratzler Shear Force, or cooked color readings among aging treatments. However, raw steaks aged 14 and 28 days had higher (P < 0.05) a* (redness) and b* (yellowness) values than steaks aged 42, 49, or 70 days. The Bottom Line: Despite minor differences in raw color, the aging period had minimal impact on overall eating quality, indicating that within the studied range, the aging process has only a minimal effect on the quality traits of biceps femoris steaks.
Keywords: beef; biceps femoris; aging